Influence of Rosemary Extract Addition in Different Phases on the Oxidation of Lutein and WPI in WPI-Stabilized Lutein Emulsions - Duoxia Xu; Zhanqun Hou; Guorong Liu; Yanping Cao; Atikorn Panya; Hang Xiao; Will Dixon (Journal of Food Quality)
The aim was to investigate rosemary extract with different addition methods affecting the physicochemical stability of WPI-coated lutein emulsions and examine the correlations between lutein degradation and WPI oxidation during storage. First, lutein emulsions containing different concentrations of rosemary extract in the oil phase were prepared. Second, lutein emulsions containing rosemary extract in the oil phase or water phase were studied along with the kinetic reaction of lutein degradation. Moreover, the impact of rosemary extract on the oxidation of WPI and their products was also determined. It was noticed that rosemary extract at 0.05 wt.% exhibited the best protection of lutein. According to the kinetics analysis of lutein degradation, the direct addition of rosemary extract in the oil phase was more suitable for retarding the degradation of lutein in emulsion than the addition in the aqueous phase due to it being partitioned at the interface. Meanwhile, it was revealed that the addition of rosemary extract in the water phase exhibited better inhibition of the WPI oxidation than addition in the oil phase. The understanding of the association and driving forces of rosemary extract in emulsion systems may be useful for the application of rosemary extract in multicomponent food systems.